2010
DOI: 10.1002/chem.201002258
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of C1 Surface Species Formed in Methane Activation on Zn‐Modified H‐ZSM‐5 Zeolite

Abstract: Solid‐state 13C magic angle spinning (MAS) NMR spectroscopy investigations identified zinc methyl species, formate species, and methoxy species as C1 surface species formed in methane activation on the zeolite Zn/H‐ZSM‐5 catalyst at T≤573 K. These C1 surface species, which are possible intermediates in further transformations of methane, were prepared separately by adsorption of 13C‐enriched methane, carbon monoxide, and methanol onto zinc‐containing catalysts, respectively. Successful isolation of each surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 88 publications
(261 reference statements)
6
85
2
Order By: Relevance
“…In this mechanism, the acylium cation was generally considered as the precursor of acetic acid, however, it is too active to be observable on zeolite-based catalysts [17] and only stabilized in superacid systems in the absence of water. Decomposition of HCOOH produces H 2 and CO 2 , [31] which in turn generates water molecules through the reverse water gas shift reaction that usually occurs in the process of methanol synthesis from CO/ CO 2 /H 2 . This suggests that water can accelerate the reaction by readily trapping the transient acylium cation to generate acetic acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this mechanism, the acylium cation was generally considered as the precursor of acetic acid, however, it is too active to be observable on zeolite-based catalysts [17] and only stabilized in superacid systems in the absence of water. Decomposition of HCOOH produces H 2 and CO 2 , [31] which in turn generates water molecules through the reverse water gas shift reaction that usually occurs in the process of methanol synthesis from CO/ CO 2 /H 2 . This suggests that water can accelerate the reaction by readily trapping the transient acylium cation to generate acetic acid.…”
mentioning
confidence: 99%
“…At the high reaction temperature, protons from either the Brçnsted acid sites or from the heterolytic dissociation of methane can react with formate species to form HCOOH. Decomposition of HCOOH produces H 2 and CO 2 , [31] which in turn generates water molecules through the reverse water gas shift reaction that usually occurs in the process of methanol synthesis from CO/ CO 2 /H 2 . [32] Although two reaction pathways proceed in parallel on the ZnZSM-5 catalyst, one of them can be preferred, depending on which reaction intermediate is predominant.…”
mentioning
confidence: 99%
“…The signal pairs at 172.5 ppm ( 13 C) and 8.3 ppm ( 1 H) in the upper panel of Figure a are attributed to formyl group (‐CHO) bonding to an oxygen atom on the catalyst . Those at 25 ppm ( 13 C) and 2.8 ppm ( 1 H) are assigned to the methylene group (‐CH 2 ‐).…”
Section: Figurementioning
confidence: 99%
“…Reactivity of the resulting zinc methyl fragment with other small molecules has been explored, in the context of stoichiometric reactions as well as potential catalytic applications. Addition of dioxygen to [Zn‐CH 3 ] + /ZSM‐5 at ambient and elevated temperature has been shown to result in the formation of zinc methoxy and zinc formate species, as monitored through NMR spectroscopic studies . On this basis, it has been shown that the chemical reactivity of [Zn‐CH 3 ] + within ZSM‐5, with molecules such as CO, CO 2 and H 2 O, has been found to be very similar to that of organozinc compounds …”
Section: Introductionmentioning
confidence: 98%